Method to Reduce Muscle Fatigue During Transcutaneous Neuromuscular Electrical Stimulation in Major Knee and Ankle Muscle Groups. (September 2015) - Sayenko, Dimitry G.; Nguyen, Robert; Hirabayashi, Tomoyo; Popovic, Milos R.; Masani, Kei
Background . A critical limitation with transcutaneous neuromuscular electrical stimulation as a rehabilitative approach is the rapid onset of muscle fatigue during repeated contractions. We have developed a method called spatially distributed sequential stimulation (SDSS) to reduce muscle fatigue by distributing the center of electrical field over a wide area within a single stimulation site, using an array of surface electrodes. Objective . To extend the previous findings and to prove feasibility of the method by exploring the fatigue-reducing ability of SDSS for lower limb muscle groups in the able-bodied population, as well as in individuals with spinal cord injury (SCI). Methods . SDSS was delivered through 4 active electrodes applied to the knee extensors and flexors, plantarflexors, and dorsiflexors, sending a stimulation pulse to each electrode one after another with 90° phase shift between successive electrodes. Isometric ankle torque was measured during fatiguing stimulations using SDSS and conventional single active electrode stimulation lasting 2 minutes. Results . We demonstrated greater fatigue-reducing ability of SDSS compared with the conventional protocol, as revealed by larger values of fatigue index and/or torque peak mean in all muscles except knee flexors of able-bodied individuals, and in all muscles tested in individuals with SCI. Conclusions . Our study has revealed improvements in fatigue tolerance during transcutaneous neuromuscular electrical stimulation using SDSS, a stimulation strategy that alternates activation of subcompartments of muscles. The SDSS protocol can provide greater stimulation times with less decrement in mechanical output compared with the conventional protocol.